2020
DOI: 10.1167/jov.20.7.10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of geometric sharpness on translucent material perception

Abstract: When judging the optical properties of a translucent object, humans often look at sharp geometric features such as edges and thin parts. An analysis of the physics of light transport shows that these sharp geometries are necessary for scientific imaging systems to be able to accurately measure the underlying material optical properties. In this article, we examine whether human perception of translucency is likewise affected by the presence of sharp geometry, by confounding our perceptual inferences about an o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
(66 reference statements)
4
12
0
Order By: Relevance
“…According to the literature, translucency can impact perceived macro-scale surface geometry of the objecttranslucent objects appearing less sharp (Chowdhury et al, 2017). Interestingly, Xiao et al (2020) have found the correlation the other way round tooexperimenting with different levels of surface relief and claiming that presence of sharp edges make materials appear less translucent. They partially attribute this to the local contrast generated by the shadows owing to high surface reliefs.…”
Section: Surface Roughness and Geometrymentioning
confidence: 99%
See 3 more Smart Citations
“…According to the literature, translucency can impact perceived macro-scale surface geometry of the objecttranslucent objects appearing less sharp (Chowdhury et al, 2017). Interestingly, Xiao et al (2020) have found the correlation the other way round tooexperimenting with different levels of surface relief and claiming that presence of sharp edges make materials appear less translucent. They partially attribute this to the local contrast generated by the shadows owing to high surface reliefs.…”
Section: Surface Roughness and Geometrymentioning
confidence: 99%
“…three objects are made of an identical material. If the proposal by Xiao et al (2020) generalizes well to all geometries, then the ranking from the most translucent to the least translucent should be the following: a cylinder, low-resolution Lucy, and a high-resolution Lucy. It is difficult to claim the latter definitively.…”
Section: Surface Roughness and Geometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Image cues as well as the amount of light exiting the volume depend on the shape complexity and thickness of a given object. For instance, it has been shown that sharp geometric details of the object impact apparent translucency [74] and the other way round, translucency affects perception of geometric edge sharpness [6]. Sawayama et al [57] have reported that "sensitivity to translucent discrimination was high when the object has rugged surfaces."…”
Section: Translucency Perceptionmentioning
confidence: 99%